Implementation of the Principal's Leadership Strategy to Improve Religious Culture Through Friday Imtaq Activities - Emiliya, Emiliya; Zainuri, Ahmad; Gani, Yasir Muslim; Annur, Saipul (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
The principal's strategy in improving religious values must start as early as possible since the declaration of programs and activities is carried out. It must also be accompanied by the cohesiveness of employees, teachers, students, and all related stakeholders. This study aims to analyze the implementation of the Principal's strategy to improve religious culture and describe the Friday imtaq activities implemented, as well as examine the factors that affect the implementation of Friday imtaq at SDN 20 Suryabumi Agrolanggen This research is expected to provide a comprehensive overview of the Principal's strategy to improve religious culture through Friday Imtaq activities as well as recommendations for enhancing the implementation of the principal strategy schools in improving religious culture. This study uses a qualitative approach with descriptive analysis. Data was collected through interviews, observations, and documentation. The research subjects involved school principals, teachers, and students. Data analysis techniques are done through data reduction, presentation, and verification. This study results in the conclusion that the implementation of the Principal's strategy in improving religious attitudes in students through habituation strategies, exemplary strategies, and partnership strategies. The implementation of Friday imtaq is in the form of reading the Qur'an, Sholawat, reading Asmaul Husna, Religious Lectures, Do'a together and the implementation of the Commemoration of Islamic Holidays, and the fact that is an obstacle to the implementation of Friday imtaq is electricity that often does not turn on, difficulty in finding speakers, and difficulty in water to carry out dhuha prayer activities which begin with ablution first.